Islamic banking selection criteria using the Analytical Hierarchy Process (AHP) / Mohammad Hakimie Nadzri, Mohammad Syafiq Zainuddin and Muhammad Asyraf Muhamad Pozi - Nadzri, Mohammad Hakimie; Zainuddin, Mohammad Syafiq; Muhamad Pozi, Muhammad Asyraf (2019)
Generally, a decision is an analytical technique to identify the optimal decision with several alternatives and risk or uncertain pattern of future events. The Analytical Hierarchy Process (AHP) is a general problem-solving methodology that is useful for complex multi-criteria decision with variables that do not have the exact numerical consequences. This research develops the understanding of the methodology and the application of AHP in life by applying it in selecting the best criteria of Islamic banking. The research study undertaken for people doing company with the bank in Northern region of Malaysia such as Perlis (Kangar), Kedah (Alor Setar), Pulau Pinang (Georgetown) and Perak (Ipoh) has a sample size of 40 customers. The objectives of the study are to identify the most important criteria in selecting Islamic banking that is considered by customers and to determine the major factor of selecting Islamic banking based on demographic variables (gender, religion, occupation). The AHP evaluates a hierarchy of criteria of the study including bank status, facilities provided, convenience, religion status, bank reputation, Sharia' issues, staff friendliness, and profitability. The result showed the best criteria chosen by all respondents were Sharia' issues. While in analyzing the major factors of selecting Islamic banking between demographic variables, the most important criteria chosen by gender was Sharia' issues for males and bank reputation for females. Next, the most important criteria chosen by religion was Sharia' issues for Muslims and convenience for non-Muslims. In addition, profitability were the most important criteria chosen by occupation for government sector, bank reputation for private sector, and religion status for other sectors.